تعليم الأصوات على أساس دراسة التقابل الصوتي بين اللغة العربية واللغة الإندونيسية - Yudhistira Ade Hermansyah (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2017)
Islam has placed the Arabic language on the main positions, because that language is the language of the two basic religion of Islam i.e. Al Quran and Hadith, and to understand the Quran and Hadith need to understand the Arabic language itself. Al Quran is kalamullah, not only addressed as a guide but more of that, Allah SWT will also give the reward of goodness for every singgle letter has been read. Therefore, every muslim considerably need a method that will help him in learning Arabic. In its development, new theories emerged in the learning and teaching of the Arabic language. Ahmad Rushdi Thuaimah points out that teaching the Arabic language should notice to the relation between Arabic with native language in Indonesia, both the similarities and the differences. Due to teaching the same thing, it is certainly easier to teach the similarities than the differences. So, to teach the Arabic language, it is advisable to lecture the sound of the Arabic language that similar with the sound of indonesiaon language before teaching the sounds of Arabic language that does not exist in Indonesian language. In other words, teaches an easy thing preferably done before a difficult thing.